Cultural Traditions and Progress - Kuzmickas, Bronius (Problemos, 1970)
The paper deals with connection and continuity questions in the realm of culture. Cultural traditions cover the widest spheres of social reality. They manifest themselves and are inherited in various forms, such as material and spiritual cultural inheritance, ways and habits of work and human communication and others. It is possible to discern in traditions progressive and conservative aspects, the division, however, is relative, depending on concrete historical conditions. Cultural traditions exert considerable influence on the progress of culture, they stir the creative efforts of people to greater activity.